Strategi Pemasaran Konvensional pada UMKM Berbasis Hobi : Studi Kasus Usaha Naya Handicraft di Kota Tebing Tinggi - Jaelani, Dede; Dalimunthe, Fitria Masbulan (STIE Bina Karya, 2025)
This study aims to analyze the conventional marketing strategies implemented by hobby-based MSMEs that have not yet adopted digital marketing. The study used a descriptive qualitative approach through a single case study with one key informant, the business owner. Data were obtained through interviews, observatios and documentation. The results indicate that marketing strategies still rely on conventional methods such as word-of-mouth promotion, participation in community activities, and maintaining personal relationships with customers. The main obstacles lie in limited time, capital, and technological capabilities. Nevertheless, the business owner is strongly motivated to maintain business continuity driven by a love of the hobby. This study illustrates that hobby-based MSMEs have significant potential for growth if supported by increased digital literacy and more innovative marketing strategies